Luminescent PtII and PtIV Platinacycles with Anticancer Activity Against Multiplatinum‐Resistant Metastatic CRC and CRPC Cell Models. Issue 9 (30th January 2020) - Lázaro, Ariadna; Balcells, Cristina; Quirante, Josefina; Badia, Josefa; Baldomà, Laura; Ward, Jas S.; Rissanen, Kari; Font‐Bardia, Mercè; Rodríguez, Laura; Crespo, Margarita; Cascante, Marta
Abstract: Platinum‐based chemotherapy persists to be the only effective therapeutic option against a wide variety of tumours. Nevertheless, the acquisition of platinum resistance is utterly common, ultimately cornering conventional platinum drugs to only palliative in many patients. Thus, encountering alternatives that are both effective and non‐cross‐resistant is urgent. In this work, we report the synthesis, reduction studies, and luminescent properties of a series of cyclometallated (C, N, N′)Pt IV compounds derived from amine–imine ligands, and their remarkable efficacy at the high nanomolar range and complete lack of cross‐resistance, as an intrinsic property of the platinacycle, against multiplatinum‐resistant colorectal cancer (CRC) and castration‐resistant prostate cancer (CRPC) metastatic cell lines generated for this work. We have also determined that the compounds are effective and selective for a broader cancer panel, including breast and lung cancer. Additionally, selected compounds have been further evaluated, finding a shift in their antiproliferative mechanism towards more cytotoxic and less cytostatic than cisplatin against cancer cells, being also able to oxidize cysteine residues and inhibit topoisomerase II, thereby holding great promise as future improved alternatives to conventional platinum drugs. Abstract : A family of luminescent Pt II and Pt IV [C, N, N′]‐cycloplatinated compounds displaying high efficacy and selectivity against a broad cancer cell panel is reported. Importantly, a complete absence of platinum cross‐resistance against metastatic CRC and CRPC multiplatinum‐resistant cell models is attained as an intrinsic property of the platinacycle (see figure).